To Understand the Mentality of The Consumer Towards The Products Packaging In Favor Of Protect The Planet - Iram Fatma; Dr. Niyati Sharma (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Using green packaging for a product is the primary achievement of adopting a green concept. Green practices, such as green packaging, have grown in importance for businesses and consumers globally as environmental concerns have increased. The goal of this study was to determine the critical elements that genuinely contribute to the propensity of Indian customers to purchase green packed FMCG product, such as wallet tissue, crisps, and mini-packs of shampoo. Five (5) qualities in all have been selected for the study based on prior research and fieldwork. A self-structured questionnaire was used for the survey, and 150 respondents who utilize green packaging were chosen using the convenience sample method. The validity, regression, correlation, and reliability of this study have all been examined help of SPSS. According to the study's findings, consumers' purchase intentions for green packaged convenience items—such as mini-packs of shampoo, chips, and wallet tissue—are positively impacted by the variables known as environment concern, environmental knowledge of green packaging, green trust, and availability. However, when it comes to mini-packs of shampoo, chips, and wallet tissue, customers' purchase intentions for green packaged convenience goods are negatively impacted by the variable known as pricing. The findings are important for Indian marketers, product and package designers, and national policymakers in developing effective and persuasive marketing plans for environmentally friendly packaging that speaks to customers' subconscious demands.